ANALISA PENGENDALIAN KUALITAS UNTUK MENGURANGI JUMLAH CACAT PRODUK PAKU PADA PT. SURABAYA WIRE MENGGUNAKAN METODE SEVEN TOOLS - Dimas Fernanda; Yoniv Erdhianto (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2022)
Quality is a factor that can increase the competitiveness of a product. With the increase in quality, it is expected that production costs will be minimal, so as to reduce waste of production costs. The failure of a product occurs due to several factors in the production process, raw materials, machines, equipment, humans, and the environment. To maintain the quality of the products produced and in accordance with the standards set, it is necessary to carry out quality control. Quality control using control maps can be used to achieve a controlled state or be within control limits so that it shows that the process is consistent. This study aims to determine the quality control of nail products using the seven tools method, to obtain data that is in accordance with the research, it is necessary to do calculations using the check sheet, histogram, Pareto chart, control chart, scatter diagram, stratification, and fishbone diagram methods